Formation of vacancy-type defects in titanium nickelide; MATEC Web of Conferences; Vol. 33 : ESOMAT 2015 – 10th European Symposium on Martensitic Transformations - Baturin A. A. Anatoly Anatolievich; Lotkov A. I. Aleksandr Ivanovich; Grishkov V. N. Viktor Nikolaevich; Lider A. M. Andrey Markovich (2015, 2015)
Title screen